PENGARUH CORPORATE SOCIAL RESPONSIBILITY, LEVERAGE, INVENTORY INTENSITY DAN UKURAN PERUSAHAAN TERHADAP AGRESIVITAS PAJAK - Tahany Nur Fadhilah; Zirman; Safitri, Devi (Jurnal Akuntansi, 2024)
This research empirically tests the influence of CSR, leverage, inventory intensity, and company size on tax aggressiveness. The secondary data is in the form of financial and sustainability reports of manufacturing companies listed on the IDX in 2019-2021. Samples were taken using a purposive sampling method with multiple linear regression analysis. The population of this study is 217 companies, with a sample of 78 companies studied for three years, so the total sample is 234. The results of this study reveal that tax aggressiveness on CSR has a negative influence, leverage has a positive impact, inventory intensity has a positive influence, and company size hasn’t impact on this.